A STUDY OF SELF-CONCEPT OF HIGHER SECONDARY SCHOOL STUDENTS IN KOLASIB DISTRICT,MIZORAM WITH REFERENCE TO THEIR ACADEMIC ACHIEVEMENT (International Journal of Food and Nutritional Sciences, 2022)
Self Concept is a person's set of observations and beliefs about himself or herself. Childhood experiences and how society perceives us both have an impact on our self-concept. These self-perceptions become more ordered and precise as we age and learn more about oneself and what is important to us. Many youths today succumb to the rising academic and social expectations, which causes mental illness and low self-esteem. Due to rising competitiveness, technological advancement, social and religious duties, and general parental expectations, children today, especially students, face enormous challenges. Therefore, it is essential to understand the various factors that influence students' self-concepts at the higher secondary level in order to foster a positive outlook and achieve better outcomes. Therefore, the study may enable the adolescent in realizing the significance of their own self-concept and in altering their perspective in order to enhance their psychological wellbeing. Additionally, the results of the study may show how important one's self-concept is to academic success.